2011
DOI: 10.1039/c1cp21015g
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative photoionization mechanism of methanol isotopologues (CH3OH, CD3OH, CH3OD and CD3OD) by iPEPICO: energetics, statistical and non-statistical kinetics and isotope effects

Abstract: The dissociative photoionization of energy selected methanol isotopologue (CH(3)OH, CD(3)OH, CH(3)OD and CD(3)OD) cations was investigated using imaging Photoelectron Photoion Coincidence (iPEPICO) spectroscopy. The first dissociation is an H/D-atom loss from the carbon, also confirmed by partial deuteration. Somewhat above 12 eV, a parallel H(2)-loss channel weakly asserts itself. At photon energies above 15 eV, in a consecutive hydrogen molecule loss to the first H-atom loss, the formation of CHO(+)/CDO(+) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 79 publications
3
66
0
Order By: Relevance
“…1c, in which a distinct peak appears at~26.3 THz, corresponding to the period of~38.0 fs. This long-lasting oscillation can only be ascribed to the motion of the vibrational wave packet on the electronic ground state of CH 3 OH + because even the lowest electronically excited state of CH 3 OH + is located 0.5 eV above the dissociation threshold for CH 2 OH + +H 15,16 and the wave packet prepared on these electronically excited states is expected to decay into the dissociation continuum.…”
Section: Resultsmentioning
confidence: 99%
“…1c, in which a distinct peak appears at~26.3 THz, corresponding to the period of~38.0 fs. This long-lasting oscillation can only be ascribed to the motion of the vibrational wave packet on the electronic ground state of CH 3 OH + because even the lowest electronically excited state of CH 3 OH + is located 0.5 eV above the dissociation threshold for CH 2 OH + +H 15,16 and the wave packet prepared on these electronically excited states is expected to decay into the dissociation continuum.…”
Section: Resultsmentioning
confidence: 99%
“…This was shown to be the case in F-atom loss in C 2 F 4 + , 9 and probably applies in CH 3 -loss from CH 3 OH + . 41 The nature of the nonstatistical fluorine atom loss from singly to triply fluorinated ethene cations has long been misunderstood. [10][11][12][13] Contrary to F-loss from C 2 F 4 + , detailed kinetic energy release studies have shown that F-loss from C 2 H 3 F + and 1,1-C 2 H 2 F 2 + is, in part, an impulsive process.…”
Section: Dynamicsmentioning
confidence: 99%
“…Therefore, it is plausible that the excited states, from which CH 2 + can eventually be generated after the migration, is higher lying electronically excited states such as theB andC states. It is then possible in the course of the migration that the wave packet initially prepared in theB and/orC states of CH 3 OH + is transferred to the electronic ground state of migrated CH 2 OH 2 + via internal conversion in a similar manner to that proceeding through the conical intersection associated with the motion of the hydrogen atom in the hydroxyl group of CH 3 OH [12,13].…”
Section: Wave Packet Motion On Potential Energy Surfacesmentioning
confidence: 98%
“…It was argued in Refs. [12,13] that CH 3 OH + prepared in the secondB and/or thirdC electronic states decays rapidly into theà state via internal conversion and that the dissociation proceeds on the potential energy surface (PES) of theà state. Therefore, it is highly probable in the present study that the wave packet is prepared in the vibrationally highly excited state of theà state of CH 3 OH + by a pump laser pulse.…”
Section: Wave Packet Motion On Potential Energy Surfacesmentioning
confidence: 99%